EFFECT OF TREATMENT OF BROILER LITTER WITH ALUMINOSILICATE - Pizarro R., Melissa (2009)
The present study aimed to evaluate the effect of treating broiler litter with active aluminosilicate on productive parameters of broiler chickens. Four hundred broilers Ross 308 of both sexes were reared for 44 days. Half of them were reared on litter treated with aluminosilicate and the other half on untreated litter. Productive performance of chicks and ammonia concentrations, atmospheric ph, litter ph, and moisture ratio of the litter were evaluated on a weekly basis. Additionally, lesions in breast and foot pads were also evaluated. Body weight gain, feed conversion index, and productive efficiency index were statistically similar between the two groups. No breast lesions were observed and the degree of lesions in foot pads was similar in the two groups. The ammonia concentrations, atmospheric ph, and litter ph were higher in the non-treated litter group showing that the litter treatment with aluminosilicate was effective in controlling ammonia levels, despite no effect was observed in the productive performance.